Bevacizumab vs Ranibizumab in Macular Edema due to Retinal Vein Occlusion: Short-term Outcomes - KURNIAWAN, CHALID (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesBevacizumab or Ranibizumab was widely used as therapy for macular edema (ME) in retinal veinocclusion (RVO) and diabetic retinopathy. The purpose of this study was to comparing short-termoutcomes for patients who received intravitreal Bevacizumab (IVB) injection or Ranibizumab (IVR)for ME due to RVO MethodsThis was observational, cross sectional study comparing patients received IVB or IVR. Primaryoutcomes data (visual acuity and central macular thickness/CMT) and secondary outcomes data(number injection and intra ocular pressure/IOP) were collected at baseline and 3 months afterinjection ResultsThere were 4 eyes in each group. There were no significant difference in mean change of visualacuity (-0.275±0.25 vs -0.15±0.5 logMAR; p=0.676) and CMT (-171.50±129.08 vs -98.25±37.67 um;p=0.345) in IVB vs IVR groups. There were also no significant difference in mean change of IOP(2±2.16 vs 2±4.69 mmHg; p=1) and number of injection (2.25±0.50 vs 1.75±0.9; p=0.401 ) in bothgroups. ConclusionIn short-term both IVB and IVB have relative similar outcomes on increasing visual acuity anddecreasing CMT in ME due to RVO